A Subtidal Box Model Based on the Longitudinal Anomaly of Potential Energy for Narrow Estuaries. An Application to the Guadalquivir River Estuary (SW Spain). Issue 5 (28th April 2020) - Cobos, M.; Baquerizo, A.; Díez‐Minguito, M.; Losada, M. A.
Abstract: The objective of the present study is to demonstrate the informative capacity of the longitudinal anomaly of potential energy (LAPE) in the analysis of the magnitude and spatiotemporal variability of estuarine processes. For this purpose, a LAPE balance equation is formulated. The LAPE integrates and varies with the vertical and longitudinal density distribution. The formulation is applied on a subtidal scale to each box or stretch of the Guadalquivir River estuary, a narrow, highly turbid, weakly stratified, and strongly anthropized estuary. Data recorded by a large network of monitoring stations in 2008 and 2009 are used to quantify advective transports as well as the transports associated with longitudinal dispersion and vertical turbulent mixing in different hydraulic regimes. In low‐river flow conditions, (river flows Q <40 m 3 s − 1 ), the magnitude of LAPE transports decreases upstream and varies locally, depending on neap‐spring tidal cycles. The direction of the net LAPE transport creates convergence zones that are particularly consistent with maximum levels of estuarine turbidity. During high‐river flows ( Q >400 m 3 s − 1 ), this convergence disappears and the maximum longitudinal density gradient moves towards the mouth. More specifically, tidal pumping ‐induced LAPE governs during these conditions and manages to compensate the sum of the mean nontidal and dispersive and differential advective LAPE transports. However, during the post‐riverflood period, the mechanisms controlling recovery downstream from the mouth are the longitudinal dispersive and differential advective LAPE transports. Furthermore, the convergence zone reappears with a longitudinal gradient of the net LAPE transport that is even greater than in low‐river flow conditions. Key Points: A balance equation of the longitudinal anomaly of the potential energy (LAPE) was derived The balance was applied in boxes to the GRE and explains the salt intrusion and turbidity maxima The dominant LAPE transports in the GRE vary spatially and also depend on the hydraulic regime